Saving Winston (Pure Flix Entertainment, 2011)
A faith-based family drama about a troubled teen who is forced to leave a self-destructive lifestyle and finds redemption through her faith in God and the rehabilitation of a rescued horse. With stunning visuals, breakthrough performances, and a beautiful soundtrack, Saving Winston is a heartfelt story about a lost soul seeking God's grace. Awarded Dove Foundations 'Family Seal of Approval' and recommended for all ages.